Odpowiedzi

2010-02-18T09:26:14+01:00
Y=x+5
y=-3x+9
-3x+9=x+5
-4x=-4/:(-4)
x=1
y=6
__________
y=2x-1
y=5x+8
3x=-9/:3
x=-3
y=-7
____________
y=x+2
y=5
5=x+2
x=3
y=5
___________
y=2x+3
y=9
6=2x/;2
x=3
y=9
2010-02-18T13:53:38+01:00
1.
y=x+5
y=-3x+9

x+5=-3x+9
x+3x=9-5
4x=4
x=1

y=1+5
y=6


2.
y=2x-1
y=5x+8

2x-1=5x+8
2x-5x=8+1
-3x=9
x=-3

y=2*(-3)-1
y=-6-1
y=-7


3.
y=-2(x+1)+1
y=3(1-2x)+8

y=-2x-2+1
y=3-6x+8

y=-2x-1
y=-6x+11

-2x-1=-6x+11
-2x+6x=11+1
4x=12
x=3

y=-2*3-1
y=-6-1
y=-7


4.
y=3-5(x-3)
y=5(1-3x)+1

y=3-5x+15
y=5-15x+1

y=-5x+18
y=-15x+6

-5x+18=-15x+6
-5x+15x=6-18
10x=-12
x=-1,2

y=-5*(-1,2)+18
y=6+18
y=24


5.
y=x+2
y=5

x+2=5
x=5-2
x=3


6.
y=2x+3
y=9

2x+3=9
2x=9-3
2x=6
x=3